Similarity Search and Applications : 12th International Conference, SISAP 2019, Newark, NJ, USA, October 2–4, 2019, Proceedings /: 12th International Conference, SISAP 2019, Newark, NJ, USA, October 2–4, 2019, Proceedings. (2019) - Unknown
No abstract available